PENINGKATAN BUDAYA LITERASI MELALUI PENGADAAN KANTIN LITERASI: SDN AIRLANGGA I/98 KECAMATAN GUBENG SURABAYA - SUNARDI, SUNARDI (Dewan Pendidikan Bondowoso, 2023)
In the school environment there is a canteen which is one of the providers of children's snacks. It is felt that the SDN Airlangga I canteen is very inadequate, this is based on the location being uncomfortable and the food menu being incomplete. Many students complain about these limitations. However, in practice, not all sellers maintain the level of cleanliness of their snacks. As well as the lack of literacy in children regarding what they already understand. This is the background for the author to carry out a school program by holding a literacy canteen to improve literacy culture at SDN Airlangga I/198 Surabaya. To improve literacy culture at SDN Airlangga I/198 Surabaya, namely by providing a literacy canteen. The canteen building was converted into a building with good air ventilation levels. And there is more spacious space, there is a library next to the canteen, comfortable seating and tables are provided. Apart from that, the equipment used in the canteen also uses clean and hygienic tools. Food serving places have also been increased and provide several types of food, which is also one of the attractions for children to buy at the literacy canteen. Apart from the building, a literacy canteen is also established in the school environment for all school residents. There were several obstacles faced in implementing the program. Some school residents do not comply with the regulations to improve literacy culture and there are still students who put their plates carelessly. However, this problem was solved by increasing the diversity of food and drinks sold in the canteen, making the literacy canteen more comfortable and writing to keep each other clean in the canteen environment. And for all residents at school, there is a culture of shame about breaking the literacy culture regulations that are being implemented at school.